Spatiotemporal Changes of Rainfall Erosivity in Loess Plateau, China. (13th March 2013) - Abd Elbasit, Mohamed A. M.; Huang, Jinbai; Ojha, CSP; Yasuda, Hiroshi; Adam, Eltayeb O.
Abstract : The reason for the severity of soil erosion in Loess Plateau can be attributed to three nonanthropogenic factors: rainfall erosivity, slope gradient, and loess soil. The rainfall erosivity is controlled by the rainfall characteristics. Generally, rainfall characteristics change drastically in space and time. The rainfall erosivity has been investigated using the modified Fournier index (MFI), annual rainfall, and precipitation concentration index (PCI). The study showed a decrease in average MFI by 10%. However, the difference between the MFI in 1960s and 1990s was found to decrease in a large area in Loess Plateau, whereas there was an increase in MFI at the high latitude. The maximum decrease in the rainfall erosivity was higher in the southeast than that in the north and west. TheP y was found to have a trend similar to the MFI, which further indicates that the MFI follows, to a high extent, the annual rainfall trend. The PCI was found to have trend opposite to MFI andP y . The PCI increased in the north and west and decreased toward the southeast. The average temporal difference in the PCI between the 1960s, and 1990s was two percent.